2012
DOI: 10.1590/s0100-29452012000300017
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização física e química de bananas produzidas em sistemas de cultivo convencional e orgânico

Abstract: RESUMO -A demanda por frutos orgânicos cresce a cada ano em todo o mundo, e a bananicultura pode apresentar crescimento nesse setor, tanto no mercado interno quanto no externo. No entanto, há falta de informações que justifiquem a produção de frutos orgânicos e que atestem as vantagens e desvantagens dos dois sistemas de cultivo. Assim, o objetivo deste trabalho foi avaliar bananas provenientes de sistema de cultivo convencional e orgânico quanto aos seus aspectos físicos e químicos. Utilizaram-se as cultivare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
1
16

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 8 publications
3
7
1
16
Order By: Relevance
“…average fresh mass of 120.62 g, being lower than that reported by Ribeiro et al (2012), which was 150.91 g, also produced in organic farming system. Carvalho et al (2011) verified the following characteristics in 'BRS tropical' fruits: 10.55 cm in length, 34.20 mm in diameter, 23.67 ºBrix (in completely yellow fruits with brown spots) and good sensory acceptability.…”
Section: Resultscontrasting
confidence: 58%
See 1 more Smart Citation
“…average fresh mass of 120.62 g, being lower than that reported by Ribeiro et al (2012), which was 150.91 g, also produced in organic farming system. Carvalho et al (2011) verified the following characteristics in 'BRS tropical' fruits: 10.55 cm in length, 34.20 mm in diameter, 23.67 ºBrix (in completely yellow fruits with brown spots) and good sensory acceptability.…”
Section: Resultscontrasting
confidence: 58%
“…Of the many questions about organic foods, the most important are those related to productivity and sensorial quality characteristics, with references to the reduced size of fruits and increased sugar contents, when fruits are obtained in an organic way (BORguINI;tORReS, 2006). Ribeiro et al (2012) verified that the chemical attributes of bananas are little affected by the cultivation system and that organic management allows greater chemical distinction of cultivars.…”
Section: Introductionmentioning
confidence: 99%
“…SS/TA ratios varied from 63.87 to 174.94. These values are close to the variations observed by Ribeiro et al (2012). The authors determined values up to full ripeness stage varying from 92.4 to 164.43 in bananas harvested from both conventional production and organic production systems.…”
Section: Resultssupporting
confidence: 85%
“…This reduction in the content of SS in fruits from plants under organic fertilization was not expected since many studies, especially those related to plants under organic management, point to a rise in the levels of SS in fruit from plants under organic management (Damatto Junior et al, 2005, Sarmento et al, 2012, not only for passion fruit, but for other tropical fruits like bananas, where organic management was found to allow a higher mean value compared to conventional cultivation system for Silver-dwarf cultivar (Ribeiro et al, 2012). In addition, yellow passion fruits that received nitrogen fertilizer as urea (Venâncio et al, 2013), showed lower SS content than the fruits receiving OF and OMF in this study.…”
Section: Pacheco Alv Et Almentioning
confidence: 99%